Morphology Design of Porous Coordination Polymer Crystals by Coordination Modulation - Umemura, Ayako; Diring, Stéphane; Furukawa, Shuhei; Uehara, Hiromitsu; Tsuruoka, Takaaki; Kitagawa, Susumu (Journal of the American Chemical Society, 2011)
The design of crystal morphology, or exposed crystal facets, has enabled the development (e.g., catalytic activities, material attributes, and oriented film formation) of porous coordination polymers (PCPs) without changing material compositions. However, because crystal growth mechanisms are not fully understood, control of crystal morphology still remains challenging. Herein, we report the morphology design of [Cu3(btc)2] n (btc = benzene-1,3,5-tricarboxylate) by the coordination modulation method (modulator = n-dodecanoic acid or lauric acid). A morphological transition (octahedron–cuboctahedron–cube) in the [Cu3(btc)2] n crystal was observed with an increase in concentration of the modulator. By suitably defining a coarse-grained standard unit of [Cu3(btc)2] n as its cuboctahedron main pore and determining its attachment energy on crystal surfaces, Monte Carlo coarse-grain modeling revealed the population and orientation of carboxylates and elucidated an important role of the modulator in determining the ⟨100⟩- and ⟨111⟩-growth throughout the crystal growth process. This comprehension, in fact, successfully led to designed crystal morphologies with oriented growth on bare substrates. Because selective crystal orientations on the bare substrates were governed by crystal morphology, this contribution also casts a new light on the unexplored issue of the significance of morphology design of PCPs.